2012
DOI: 10.1038/jid.2011.455
|View full text |Cite
|
Sign up to set email alerts
|

The Organotelluride Catalyst (PHTE)2NQ Prevents HOCl-Induced Systemic Sclerosis in Mouse

Abstract: Systemic sclerosis (SSc) is a connective tissue disorder characterized by skin and visceral fibrosis, microvascular damage, and autoimmunity. HOCl-induced mouse SSc is a murine model that mimics the main features of the human disease, especially the activation and hyperproliferation rate of skin fibroblasts. We demonstrate here the efficiency of a tellurium-based catalyst 2,3-bis(phenyltellanyl)naphthoquinone ((PHTE)(2)NQ) in the treatment of murine SSc, through its selective cytotoxic effects on activated SSc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In this model, damage to endothelial cells occur quite early, as suggested by the high amounts, compared to untreated mice, of endothelial microparticles as well as sVCAM and sE-selectin found in the bloodstream of HOCl-treated animals [98,159,160].…”
Section: Hocl-injected Micementioning
confidence: 96%
See 1 more Smart Citation
“…In this model, damage to endothelial cells occur quite early, as suggested by the high amounts, compared to untreated mice, of endothelial microparticles as well as sVCAM and sE-selectin found in the bloodstream of HOCl-treated animals [98,159,160].…”
Section: Hocl-injected Micementioning
confidence: 96%
“…Moreover, propylthiouracil (PTU) can prevent the development of cutaneous and lung fibrosis in these mice through a direct effect on ROS metabolism and an indirect effect on thyroid function inhibition [162]. The specific targeting of activated hyperproliferative fibroblasts has also been investigated successfully in these mice by the use of pro-oxidant drugs that raise hydrogen peroxide (H 2 O 2 ) levels of diseased fibroblasts above a lethal threshold [132,159,160]. Indeed, the use of arsenic trioxide in mice with HOClinduced SSc limited dermal thickness and inhibited collagen deposition in both skin and lungs, while vascular damages and immune activation were reduced.…”
Section: Hocl-injected Micementioning
confidence: 99%
“…In another recent study, the ef fi ciency of a tellurium-based catalyst, 2,3-bis(phenyltellanyl)naphthoquinone ((PHTE)(2) NQ), in the treatment of HOCl-induced murine model of SSc was demonstrated. (PHTE)(2)NQ ef fi ciency is linked to the selective pro-oxidative and cytotoxic effects of this compound on hyperproliferative fi broblasts [ 65 ] . Another putative antioxidant molecule, a -melanocyte-stimulating hormone, suppressed bleomycininduced oxidative stress, reduced skin fi brosis and collagen content, and increased tissue levels of superoxide dismutase 2 (SOD2) and heme oxygenase-1 in a murine model of SSc and was, therefore, suggested as a potential therapy for SSc [ 66 ] .…”
Section: Antioxidant Treatmentsmentioning
confidence: 99%
“…Prompt, global, and dynamic increases in O-GlcNAc modifications are observed on nucleocytoplasmic proteins on exposure to different forms of cellular stress (oxidative, thermal, chemical, and biological), and the increase was observed to be protective to the cell contributing to stress tolerance. 58 It has been observed that O-GlcNAcylation increases the stability of heat shock 6 Glycobiology Insights family proteins HSP70 and HSP40. O-GlcNAc transferase knockdown reduced HSP70 and HSP40 levels.…”
Section: N-glycosylationmentioning
confidence: 99%
“…5 However, during mild ER stress, cells do not undergo apoptosis and they can continue to proliferate. 6 Three ER-localized proteins (protein kinase RNA-like endoplasmic reticulum kinase [PERK], inositol-requiring enzyme 1 [IRE1], and activating transcription factor 6 [ATF6]) monitor the UPR in the ER lumen and, on activation, regulate downstream responses to this stress. Binding immunoglobulin protein (BiP, also called GRP78) is bound to PERK, IRE1, and ATF6 and in quiescent cells inactivates these pathways.…”
Section: Er Stress and Upr In Cell Fate Decisionsmentioning
confidence: 99%